Cadmium and other metallic contaminants in cacao: Update on current knowledge and mitigation strategies☆ - Letort Fabien; Chavez Eduardo; Cesaroni Camille; Castillo-Michel Hiram; Sarret Géraldine (Oilseeds and fats, crops and lipids)
Cadmium (Cd) is a non-essential metal classified as class 1 carcinogen, which can induce detrimental effects for humans. Food is the main route of Cd exposure for the general population (except smokers). Chocolate products account for 4% and 9% of the dietary Cd intake for adults and children, respectively, in Europe. Since 2019, the EU limits Cd concentration in chocolate. The maximum permitted concentration (MPC) varies from 0.30 to 0.80 mg Cd kg−1 depending on the% of total cocoa solids in the final product. Cacao (Theobroma cacao L.) producers in Latin America and the Caribbean, who provide 19.4% of global cacao production, are strongly impacted because a significant fraction of their production exceeds these limits. In this review, the current knowledge on the factors influencing the soil Cd enrichments and Cd phytoavailability is discussed. The Cd transfer to cacao trees and to beans, and the responses of cacao trees to Cd exposure are also presented. Then, various mitigation strategies, including post-harvest treatments, soil amendments, microbial remediation (or bioremediation), breeding programs and grafting, are summarized. We also discuss the transfer of knowledge to stakeholders in the cacao supply chain. Finally, current knowledge on the presence of other metallic contaminants in cacao beans, particularly nickel (Ni), is reviewed.